1990
DOI: 10.1038/nbt1090-939
|View full text |Cite
|
Sign up to set email alerts
|

Insect Resistant Cotton Plants

Abstract: We have expressed truncated forms of the insect control protein genes of Bacillus thuringiensis var. kurstaki HD-1(cryIA(b) and HD-73 (cryIA(c) in cotton plants at levels that provided effective control of agronomically important lepidopteran insect pests. Total protection from insect damage of leaf tissue from these plants was observed in laboratory assays when tested with two lepidopteran insects, an insect relatively sensitive to the B.t.k. insect control protein, Trichoplusia ni (cabbage looper) and an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
251
1
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(266 citation statements)
references
References 14 publications
7
251
1
4
Order By: Relevance
“…Reverse transcriptase-PCR with the total RNA isolated from the electroporated protoplast indicated that, in the case of unmodified cryIAb, there are two exon͞intron donors (gt) and two intron͞exon acceptors (ag) lying beyond 1350 bp in the cryIAb gene that result in generation of shorter transcripts when compared with the modified cryIAb gene, where the sequence around gt has been altered. Both the native as well as the modified cryIAc gene of Perlak et al (7) in the same region contained four such intron͞exon acceptors (ag) and eight and seven exon͞intron donors (gt), respectively. Site detection analysis was carried out with the help of the PCGENE program, where the cutoff values for exon͞intron (donor) junctions and intron͞exon (acceptor) junctions were set at Ϫ15 and Ϫ22, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcriptase-PCR with the total RNA isolated from the electroporated protoplast indicated that, in the case of unmodified cryIAb, there are two exon͞intron donors (gt) and two intron͞exon acceptors (ag) lying beyond 1350 bp in the cryIAb gene that result in generation of shorter transcripts when compared with the modified cryIAb gene, where the sequence around gt has been altered. Both the native as well as the modified cryIAc gene of Perlak et al (7) in the same region contained four such intron͞exon acceptors (ag) and eight and seven exon͞intron donors (gt), respectively. Site detection analysis was carried out with the help of the PCGENE program, where the cutoff values for exon͞intron (donor) junctions and intron͞exon (acceptor) junctions were set at Ϫ15 and Ϫ22, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To increase the expression level of the Bt genes in transgenic plants, Bt genes have been extensively modified, fused to highly efficient promoters and introduced into tobacco (Perlak et al 1991, Sutton et al 1992, tomato (Perlak et al 1991), potato (Adang et al 1993), cotton (Perlak et al 1990), rice (Fujimoto et al 1993) and maize (Koziel et al 1993). To achieve a high expression of these prokaryotic genes in higher plants, modification of the coding sequence, such as removal of ATTTA sequences and use of the preferred codons, was undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the coding sequences successfully enhanced plant expression of Bt genes (Perlak et al 1990, Sutton et al 1992, Adang et al 1993, Koziel et al 1993.…”
Section: Introductionmentioning
confidence: 99%
“…Koul et al, 2014 Total larval mortality of 2 insect pests (Trichoplusia ni and Spodoptera exigua ) and high levels of plant protection have been observed on transgenic cotton plants expressing cry1Ac or cry1Ab genes from Bt var Kurstaki (HD-1 and HG-73, respectively). Perlak et al, 1990 Different cry toxins (cry1Ab, cry1ac or cry1B) have also been expressed in cereal crops like rice Cheng, Sardana, Kaplan, Altosaar 1998;Datta et al, 1998;Breitler 2001, Khanna, Raina 2002Ramesh, Nagadhara, Reddy, Rao 2004, maize Bohorova et al, 1999Armstrong 1995, Koziel et al, 1993and sorghum.Girijashankar et al, 2005 According to the reports, up to 100% larval mortality of the target insect pests as well as substantially reduced plant damage was observed on the transgenic plants of these crops.…”
Section: Insect Resistance Evaluation Of the Cry1ac Transgenic Pea Linesmentioning
confidence: 99%
“…Bravo et al, 2011 In line with this gap, we have reported the successful development of transgenic pea lines expressing cry1Ac gene from Bacillus thuringiensis. Negawo et al, 2013 The cry1Ac gene Cheng, Sardana, Kaplan, Altosaar 1998;Sardana 1996 is one of the commonly used Bt cry genes to develop transgenic lines in many plant species such as tobacco, cotton, maize, soybean, tomato and rice, Cheng, Sardana, Kaplan, Altosaar 1998;Perlak 1990;Bohorova 1999;Stewart Jr CN 1996;Mandaokar et al, 2000 to become resistant to Lepidopteran pests. Hofte, Whiteley 1998;Crickmore 1998 Lepidopteran insect pests belong to the major pests of pea and many other legume species as they cause significant yield losses under field conditions.…”
Section: Introductionmentioning
confidence: 99%